Norepinephrine modulates calcium dynamics in cortical oligodendrocyte precursor cells promoting proliferation during arousal in mice - Lu, Tsai-Yi; Hanumaihgari, Priyanka; Hsu, Eric T.; Agarwal, Amit; Kawaguchi, Riki; Calabresi, Peter A.; Bergles, Dwight E. (Nature neuroscience, 2023)
Oligodendrocytes, the myelinating cells of the central nervous system (CNS), are generated from oligodendrocyte precursor cells (OPCs) that express neurotransmitter receptors. However, the mechanisms that affect OPC activity in vivo and the physiological roles of neurotransmitter signaling in OPCs are unclear. In this study, we generated a transgenic mouse line that expresses membrane-anchored GCaMP6s in OPCs and used longitudinal two-photon microscopy to monitor OPC calcium (Ca2+) dynamics in the cerebral cortex. OPCs exhibit focal and transient Ca2+ increases within their processes that are enhanced during locomotion-induced increases in arousal. The Ca2+ transients occur independently of excitatory neuron activity, rapidly decline when OPCs differentiate and are inhibited by anesthesia, sedative agents or noradrenergic receptor antagonists. Conditional knockout of α1A adrenergic receptors in OPCs suppresses spontaneous and locomotion-induced Ca2+ increases and reduces OPC proliferation. Our results demonstrate that OPCs are directly modulated by norepinephrine in vivo to enhance Ca2+ dynamics and promote population homeostasis.
Gesehen am 08.11.2023